Istilah-Istilah Kuliner dalam Ritual Neloni di Kabupaten Malang: Studi Etnolinguistik (Sutasoma : Jurnal Sastra Jawa, 2022)
This study aims to reveal lexical and cultural meanings of neloni and describes the culinary terms within the ritual in Malang district. Neloni is a ritual for three months old baby in Java. The data source are the society of Desa Pandanajeng, Tumpang, Malang, East Java and other relevant literary sources. The data in this study is the information of lexical and cultural meanings of neloni along with the culinary terms in words or phrases within the ritual. The researchers utilize interview techniques to obtain the data and record the interview. In analyzing the data, the researchers employ agih method andBagi Unsur Langsung (BUL) technique. The results uncover that neloni has lexical meaning as three months celebration for the baby’s birth and the mommy’s pregnancy. Meanwhile, the cultural meaning reflects three kindness from God. They are character, ability, and feeling/emotions. The cultural terms involved in the ritual are ayam keting, jangan lodheh, jangan petang werno, jenang sengkolo, kuluban, trancam, tumpeng kuning, tumpeng putih and urap. Each culinary terms have lexical and cultural meanings. Keywords: Culinary term; ritual of neloni; ethnolinguistics